Sekularisasi dalam Perspektif Tauhid: Analisis Pemikiran Nurcholish Madjid tentang Desakralisasi dan Pembaharuan Islam: Secularization in the Perspective of Tawhid: An Analysis of Nurcholish Madjid’s Thought on Desacralization and Islamic Renewal - Mohamad Asrori Mulky (Al-Ma‘ani: Journal of Islamic Studies, 2026)
This study aims to critically examine the concept of secularization in the thought of Nurcholish Madjid by situating it within the framework of tawhid. The research is motivated by the stagnation of Islamic thought amid modern challenges and the widespread misunderstanding of secularization, which is often equated with secularism. This study employs a qualitative method using library research, combined with a descriptive-analytical approach and content analysis techniques. The findings reveal that secularization, in Madjid’s perspective, does not imply the separation of religion from public life, but rather a process of desacralization of worldly matters that have been excessively sanctified. In this context, secularization is understood as a logical consequence of tawhid, affirming that only God is absolute. However, critical analysis indicates the presence of conceptual ambiguities, particularly in the use of the term secularization and the distinction between the sacred and the profane. Therefore, while the concept remains relevant in promoting Islamic intellectual reform, it requires methodological refinement to prevent it from drifting toward secularism or relativism.